Quantum chemical calculation employed for investigation mesitylene compound - Kareem, Rebaz Obaıd; Azeez, Yousif Hussein; Hamad, Othman; Omer, Rebaz; Othman, Khdir; Ahmed, Lana; Kaygılı, Omer (Niyazi BULUT, 2024)
The purpose of this study was to provide a theoretical evaluation of the benzene ring, and three methyl groups (CH3) that give the chemical its name (mesitylene, or C9H12) using quantum computation. The theoretical characteristics of the research were investigated using Gaussian software (DFT)/B3LYP employing 3-21G STO cc-pVDZ VDD basis sets. The mesitylene structures' shape was then optimized using this knowledge. The calculations for the electronic properties, including excitation energies, wavelengths, EHOMO and ELUMO energies, (DOS), Molecular Orbital Theory (MOT), electronic charge destruction, FT-IR, and the RAMAN spectrum, were carried out by DFT. The thermochemistry results, which include entropy (S), molar heat capacity (Cv), and thermal energy (E) complement the electronic properties. The STO/B3LYP base set has an excellent value for the BG energy, which is calculated to be 6.562 eV. This result agrees with previous research 6.22 eV.
Keywords: Metrology; Applied and Industrial Physics; Metroloji; Uygulamalı ve Endüstriyel Fizik